2021
DOI: 10.1177/03635465211033995
|View full text |Cite
|
Sign up to set email alerts
|

Quadriceps Tendon Versus Hamstring Tendon Autografts for Anterior Cruciate Ligament Reconstruction: A Systematic Review and Meta-analysis

Abstract: Background: Autograft choice in anterior cruciate ligament reconstruction (ACLR) remains controversial, with increasing interest in the usage of quadriceps tendon (QT) autograft versus traditional hamstring tendon (HT) use. The current study undertakes an in-depth review and comparison of the clinical and functional outcomes of QT and HT autografts in ACLR. Hypothesis: The QT autograft is equivalent to the HT autograft and there will be little or no significant difference in the outcomes between these 2 autogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
29
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 62 publications
(97 reference statements)
6
29
1
Order By: Relevance
“…Previous studies examining the use of BTB autografts in primary as well as revision ACL reconstruction have found that BTB autografts provide excellent clinical and functional outcomes and are associated with low measured laxity, rapid graft incorporation, low complication and failure rates, favorable biomechanical properties, faster return to sports and/or activity, and high PRO measures (PROMs) postoperatively. 3,12,16,26 Fewer data exist regarding the use of ASTQT autografts in revision ACL reconstruction. However, a study by Hunnicutt et al 17 found that ASTQT autograft for revision ACL reconstruction exhibited acceptable early and intermediate-term clinical and functional outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies examining the use of BTB autografts in primary as well as revision ACL reconstruction have found that BTB autografts provide excellent clinical and functional outcomes and are associated with low measured laxity, rapid graft incorporation, low complication and failure rates, favorable biomechanical properties, faster return to sports and/or activity, and high PRO measures (PROMs) postoperatively. 3,12,16,26 Fewer data exist regarding the use of ASTQT autografts in revision ACL reconstruction. However, a study by Hunnicutt et al 17 found that ASTQT autograft for revision ACL reconstruction exhibited acceptable early and intermediate-term clinical and functional outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…8,29 Recently, all-soft tissue quadriceps tendon (ASTQT) autografts have become a more popular graft type secondary to their favorable biomechanical properties and comparable clinical and functional outcomes and graft survival compared with HT autografts in primary ACL reconstruction. 5,6,11,[22][23][24][25][26][27] Interest has further grown in ASTQT autograft use in revision cases; however, data are limited, and authors have expressed concern about the patients' ability to tolerate a secondary insult to the extensor mechanism after a primary BTB autograft. 22 The purpose of this study was to evaluate the ASTQT autograft in revision ACL reconstruction in athletes compared with BTB autograft with a minimum 2-year followup.…”
mentioning
confidence: 99%
“…The autograft was selected based on biomechanical and individual criteria. When it was, from the athlete point of view of the participant and/or due to the type of activity, important to preserve the hamstring complex and, thus, to avoid damage to the knee flexor compartment [ 22 ], a quadriceps graft was usually selected. From a biomechanical point of view, small hamstring tendon sizes may not be suitable for a graft in certain patients [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…Semitendinosus (alone or in combination with gracilis; = hamstring) and quadriceps femoris tendon grafts show comparable graft survival rates, clinical stability and functional outcomes when compared to each other [ 14 , 15 ]. In contrast functional outcomes, such as knee extensor muscle strength deficiency, might be superior in knees which were reconstructed with a hamstring graft than in those with a quadriceps graft [ 14 , 22 ]. Although numerous randomised controlled and observational studies have compared quadriceps and hamstring grafts, little is known on potential differences between hamstring and quadriceps graft-based reconstructions on return to sport success rates.…”
Section: Introductionmentioning
confidence: 99%
“…In highly active patients (Tegner-activity-level ≥ 7), the re-rupture rate increased to 37.5% in the HT group while remaining constant in the QT cohort (22.2%). Results of recent systematic reviews and meta-analyses are inconclusive, reporting either higher [ 52 , 94 ] or equal [ 21 , 91 , 120 ] re-rupture and revision surgery rates for HT versus QT.…”
Section: Introductionmentioning
confidence: 99%